MECHANISMS RELATING GLYCEMIC STRESS TO AGE-RELATED MACULAR DEGENERATION. (11th November 2018) - Rowan, S; Jiang, S; Chang, M; Bejarano, E; Smith, D; Taylor, A
Abstract: Age-related macular degeneration (AMD) is a leading cause of vision loss worldwide. Individuals that consume Western diets, containing large amounts of high glycemic index carbohydrates, are at dramatically increased risk for AMD. To understand disease pathogenesis, we aged wildtype C57BL/6J mice fed matched high or low glycemic diets. Mice that consumed high glycemic diets developed AMD-like pathologies, whereas mice consuming low glycemic diets, or whose diets were switched from high to low glycemic diets midway through study had normal eyes. We have uncovered several mechanisms related to disease pathogenesis or protection from disease. High glycemic stress causes accumulation of advanced glycation end-products and lipid peroxidation products systemically and in the eye, leading to impaired autophagic and proteasomal proteolytic capacities of retinal cells. Low glycemic diets alter the composition of gut microbiota and circulating metabolites leading to neuroprotection of the retina. Novel biomarkers of glycemia may impact AMD diagnosis and treatment.